Role of National Bank for Agriculture and Rural Development (NABARD) and Small Industries Development Bank of India (SIDBI) in Indian Microfinance (Global Journal of Human-Social Science, 2016)
Economists have long agreed that access to finance plays an essential role in the process of dipping the inequality in wealth distribution, it enhancing the household income and provide better employment opportunities. Microfinance in India is now mounting and covering wider boundaries more importantly it gets appreciations as a tool to reduce poverty. It has become a critical tool for reaching all those under privileged groups such as women, socially and economically backward classes for the purpose of empowerment and providing access to the financial services. It is a cost effective mechanism for providing financial services to the poor. This working paper tries to outline the prevailing conditions of the Microfinance in India. Further the paper the paper is highlighting the financial & promotional support by NABARD and SIDBI in the sector of microfinance.
Keywords: microfinance; self help group; NABARD; refinance; SIDBI and MFIs